Spatial Concentration of Manufacturing Firms in China - Steven Brakman; Harry Garretsen; Zhao Zhao (Center for Economic Studies and ifo Institute (CESifo), 2014)
Applying the methodology developed by Duranton and Overman (2005, 2008), we analyze localization and dispersion of firms in China. Using a unique and detailed dataset on manufacturing firms in China, we are able to follow the changes in location patterns of firms between 2002 and 2008. Our analysis shows that firms in China are more localized than in the UK or Japan. Localization is comparable to that in the US, and takes place at relative small scales that are consistent with the size of Chinese cities. Localization increases rapidly, even in the relative short period between 2002 and 2008, especially new entrants localize. Private firms, firms from Hong-Kong, Macao and Taiwan, and foreign firms are more localized than state-owned firms. Our findings are consistent with the notion that China is increasingly liberalizing its economy, enabling (profit seeking) manufacturing firms to benefit from agglomeration economies.
Keywords: F23; R12; L70; 330; spatial concentration; China; manufacturing firms; localization